1994
DOI: 10.1128/aac.38.3.528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro exoenzyme-suppressing activities of azithromycin and other macrolide antibiotics against Pseudomonas aeruginosa

Abstract: The inhibitory effects of azithromycin (AZM), a new 15-membered macrolide antibiotic, on the production of exotoxin A, total protease, elastase, and phospholipase C by Pseudomonas aeruginosa were determined, and the virulence-suppressing effects of AZM were compared with those of erythromycin (EM), roxithromycin (RXM), and rokitamycin (RKM). The elfect of exposure ofP. aeruginosa PA103 or B16 in cultures to sub-MICs of these macrolide antibiotics on the production of exoenzymes was determined. AZM suppressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 33 publications
(32 reference statements)
7
46
0
Order By: Relevance
“…Previous studies suggested that sub-inhibitory levels of macrolides could inhibit bacterial virulence factors in vitro [11,12]. LAGROU et al [19] also reported that sub-MIC of erythromycin reduced the haemolytic activity of PLY by MRSP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies suggested that sub-inhibitory levels of macrolides could inhibit bacterial virulence factors in vitro [11,12]. LAGROU et al [19] also reported that sub-MIC of erythromycin reduced the haemolytic activity of PLY by MRSP.…”
Section: Discussionmentioning
confidence: 96%
“…Some recent reports have shown the effects of sub-minimum inhibitory concentrations (sub-MIC) of macrolides on bacterial virulence factors [11]. For example, sub-MIC of azithromycin (AZM) inhibited exotoxin A, total protease, elastase and phospholipase C production by Pseudomonas aeruginosa without affecting the growth of P. aeruginosa [12].…”
mentioning
confidence: 99%
“…This was an unexpected finding, considering the high levels of resistance that P. aeruginosa shows toward these drugs, and general anti-inflammatory effects associated with macrolides were suggested to account for the positive results (312). However, in vitro testing with subinhibitory concentrations of macrolides indicated an additional effect of their application on reduction of P. aeruginosa virulence factor expression, including decreased production of exotoxin A, proteases, elastase, DNase, leukocidin, and phospholipase C (313)(314)(315). Positive outcomes from sub-MIC AZM treatments against P. aeruginosa in a murine pneumonia model provided further laboratory evidence that macrolides could affect the physiology of the bacteria without inhibiting their growth in vivo (316).…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 99%
“…The strain was isolated clinically from a blood sample at Nagasaki University Hospital (Nagasaki, Japan) [7,8]. Lipopolysaccharide (LPS) extracted from P. aeruginosa serotype 10 was obtained from Sigma Chemical Co. (St Louis, MO).…”
Section: Bacterial Strain and Lpsmentioning
confidence: 99%